Human respiratory tract protection with the help of electret fiber filters - Kravtsov Александр Геннадьевич; Zotov Сергей Валентинович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
The work deals with solving actual problem in materials science, i.e. the creation of new generation of filtering materials for the individual means of protection breathing organs – the electret polyolefine fibrous materials, produced by a solute-free melt blowing technology. A combination of parameters has been determined, under which polyolefine fibrous materials acquire characteristics for filtration of aerosols, acceptable for light respirators. The role of forced electrization in arising of electret charge in fibrous materials has been estimated. The possibility of production fibers less than 10 pm in diameter from low-density polyethylene and less than 1 pm - from polypropylene have been experimentally proved. Also, the possibility of forming electret charge in the fibers with the effective surface density 20 nC/cm2 has been proved. The penetration coefficient 0.01 % and aerodynamic resistance 40 Pa have been achieved for the electret fibrous filtering materials from polypropylene (fiber diameter 0.5 pm, packing density 0.20–0.23, electret charge density about 15 nC/cm2). Results of work have been realized in production of electret polyolefine filtering materials for light respirators.